On the enzymatic incorporation of an imidazole nucleotide into DNA. Issue 20 (9th May 2017) - Röthlisberger, Pascal; Levi-Acobas, Fabienne; Sarac, Ivo; Marlière, Philippe; Herdewijn, Piet; Hollenstein, Marcel
Abstract : We have evaluated the possibility for using an imidazole modified nucleoside triphosphate for the enzymatic construction of artificial metal base pair with view on an expansion of the genetic code. Abstract : The expansion of the genetic alphabet with an additional, artificial base pair is of high relevance for numerous applications in synthetic biology. The enzymatic construction of metal base pairs is an alluring strategy that would ensure orthogonality to canonical nucleic acids. So far, very little is known on the enzymatic fabrication of metal base pairs. Here, we report on the synthesis and the enzymatic incorporation of an imidazole nucleotide into DNA. The imidazole nucleotidedIm is known to form highly stabledIm -Ag + -dIm artificial base pairs that cause minimal structural perturbation of DNA duplexes and was considered to be an ideal candidate for the enzymatic construction of metal base pairs. We demonstrate thatdImTP is incorporated with high efficiency and selectivity opposite a templatingdIm nucleotide by the Kf exo − . The presence of Mn 2+, and to a smaller extent Ag +, enhances the efficiency of this polymerization reaction, however, without being strictly required. In addition, multiple incorporation events could be observed, albeit with modest efficiency. We demonstrate that thedIm -M n + -dIm cannot be constructed by DNA polymerases and suggest that parameters other than stability of a metal base pair and its impact on the structure of DNA duplexes govern the enzymatic formation of artificial metal base pairs.